How do you solve #4 x^2 – 3x + 3 = 0# using the quadratic formula?

1 Answer
May 1, 2016

Answer:

The solutions for the equation are :
#=(3+sqrt(-39))/8#
#=(3-sqrt(-39))/8#

Explanation:

#4x^2 -3x + 3 = 0#

The equation is of the form #color(blue)(ax^2+bx+c=0# where:
#a=4, b=-3, c=3#

The Discriminant is given by:

#Delta=b^2-4*a*c#

# = (-3)^2-(4 * 4 *3)#

# = 9 - 48=- 39 #

The solutions are found using the formula
#x=(-b+-sqrtDelta)/(2*a)#

#x = (-(-3)+-sqrt(-39))/(2*4) = (3+-sqrt(-39))/8#

The solutions are:
#=(3+sqrt(-39))/8#
#=(3-sqrt(-39))/8#